IMPLEMENTASI PROGRAM PELIBATAN DAN PEMBERDAYAAN MASYARAKAT PT TIRTA INVESTAMA AQUA BABAKAN PARI - Janah, Raisatul; Sukarelawati, Mrs.; Agustini, Mrs. (Universitas Djuanda Bogor, 2019)
This study aims to find out Muslim social behavior towards LGBT in the film Cinta Fiisabiilillah on Youtube. This study used a qualitative approach and descriptive analysis research method by carrying out data collection techniques using primary data and secondary data. Primary data is in the form of observations and interviews. While secondary data is in the form of documentation. The object of research is the Cinta Fiisabiilillah Film. The results showed that Muslim social behavior towards LGBT in the film Cinta Fiisabiilillah was to accept and embrace it to hijrah Fiisabiilillah together and not move away because of its poor past.Keywords: Behavior, LGBT, Film